ANALISIS PENGARUH QRIS PADA PENGELUARAN IMPULSIF DAN RASIONAL GENERASI Z - Cynthia Dikna Sari; Rifka Audinasari; Fajriana Khusnul Khatimah (Taksasila Edukasi Insani, 2026)
This study aims to analyze the dynamics of Generation Z's financial behavior in the digital era by examining the influence of QRIS availability, financial knowledge, savings and loan instruments, and investments on impulsive and rational spending. Using regression analysis, the results show that the ease of transactions through QRIS creates a behavioral paradox, where this system significantly encourages impulsive spending (55% of the variation in impulsivity is explained by QRIS use) while simultaneously weakening rational spending control.The research findings confirm that financial knowledge serves as a vital cognitive control mechanism; high financial literacy is negatively correlated with impulsive spending and positively correlated with rational spending. Furthermore, this study reveals the dual impact of owning financial instruments (savings and loans), which can trigger impulsive consumption if viewed solely as liquidity, but can foster rationality when managed within a future planning framework. Investments prove to be the most effective strategic instrument in curbing impulsive behavior, by shifting Generation Z's paradigm from viewing money as a consumptive medium of exchange to a long-term asset of value. Overall, this study concludes that the efficiency of digital payment technology requires mature financial literacy and investment discipline to prevent a shift in consumption patterns to unplanned ones.Keywords: QRIS, Impulsive Spending, Rational Spending, Financial Knowledge, Generation Z, Investment.